Karyotype of Polyommatus (Agrodiaetus) eriwanensis Forster, 1960 and taxonomic position of P. (A.) interjectus de Lesse, 1960 (Lepidoptera, Lycaenidae) - Lukhtanov, Vladimir A. (Comp Cytogenet, 2019)
Abstract. The karyotype of Polyommatus (Agrodiaetus) eriwanensis Forster, 1960 from the type locality (“Eriwan” [Yerevan, Armenia]) and other localities in Armenia was investigated. The number of chromosomal elements (bivalents+ multivalents) observed in male meiosis I was found to vary from 29 to 34. In individuals with n = 34, all observed elements were represented by bivalents. In other specimens, heterozygosity for different number of chromosomal fusions resulted in multivalent formation at MI stage and consequently in a lower number of recognizable chromosomal elements. We show that all karyotype peculiarities of P. (A.) interjectus de Lesse, 1960 (n = 29–32) from Turkey are similar to those in A. eriwanensis. The butterflies of these taxa have allopatric distribution and can be considered as conspecific.